2018
DOI: 10.3389/fpsyg.2018.02358
|View full text |Cite
|
Sign up to set email alerts
|

East Asian Young and Older Adult Perceptions of Emotional Faces From an Age- and Sex-Fair East Asian Facial Expression Database

Abstract: There is increasing interest in clarifying how different face emotion expressions are perceived by people from different cultures, of different ages and sex. However, scant availability of well-controlled emotional face stimuli from non-Western populations limit the evaluation of cultural differences in face emotion perception and how this might be modulated by age and sex differences. We present a database of East Asian face expression stimuli, enacted by young and older, male and female, Taiwanese using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 85 publications
1
11
0
Order By: Relevance
“…Our findings also help to explain the results of a recent study that indicated Easterners tend to have three categories of emotion faces: happy, sad/angry/disgusted, and fearful/surprised 36 . Happy expressions can be distinguished uniquely by an upturned mouth, and despite Easterners having some difficulty decoding mouth information, happy mouths are different from all other emotions and are thus easier to decode.…”
Section: Discussionsupporting
confidence: 72%
“…Our findings also help to explain the results of a recent study that indicated Easterners tend to have three categories of emotion faces: happy, sad/angry/disgusted, and fearful/surprised 36 . Happy expressions can be distinguished uniquely by an upturned mouth, and despite Easterners having some difficulty decoding mouth information, happy mouths are different from all other emotions and are thus easier to decode.…”
Section: Discussionsupporting
confidence: 72%
“…Second, we asked the participants to passively view the facial expression pictures in the emotional arousal state, but we did not record the responses of subjective emotion level during or after performing the emotional arousal task. Because the emotional arousal after the consecutive presentation of emotional facial expressions has been documented in the literature (Lang et al, 2005; Tu et al, 2018), we assumed that the emotion was successfully induced in our task, which was orally confirmed by the bereaved participants. Third, the baseline FFMQ assessment before the MBCT course might be with poor precision (Chiesa, 2013; Davidson, 2010), for the possibility that the bereaved participants with high levels of emotional entanglements did not adequately comprehend the mindfulness questionnaire.…”
Section: Discussionmentioning
confidence: 87%
“…The International Affective Picture System (IAPS) is a standardized instrument for the induction of emotional states (Lang, Bradley, & Cuthbert, 2005). The current study used datasets of the Taiwanese version of IAPS (T‐IAPS) to induce the emotional arousal in participants (Tu, Lin, Suzuki, & Goh, 2018). Therefore, 30 pictures of negative facial expression and 30 pictures of neutral facial expression were drawn randomly from the T‐IAPS as continuous visual stimuli in the emotion‐arousal session.…”
Section: Methodsmentioning
confidence: 99%
“…Riegel et al, 2015;Scott et al, 2019) or faces (e.g. Prada et al, 2018;Tu et al, 2018). In an attempt to present a broader range of stimuli sets, Krumhuber et al (2017) systematically reviewed dynamic datasets of facial expressions.…”
Section: The Range Of Available Setsmentioning
confidence: 99%